2011
DOI: 10.1097/psy.0b013e3182155c83
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Inhibition Is Associated With Airway Hyperresponsiveness but not Atopy in a Monkey Model of Asthma

Abstract: Objective To determine whether indicators of behavioral inhibition and cortisol responses to stressful situations, obtained in infancy, were associated with asthma-related measures (atopy and airway hyper-responsiveness) approximately two years later. Methods Measures reflecting inhibited temperament and cortisol response following a 25-hr separation from mother and relocation to a novel room were obtained for 21 rhesus monkeys (mean age 109 days, range 91–122). Inhibited temperament was measured by reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 47 publications
2
27
0
Order By: Relevance
“…Decades of research have likewise demonstrated close similarity between humans and rhesus monkeys in behavioral and physiological measures of behavioral inhibition [16], [17]. In fact, in a recent retrospective study in our laboratory, we found that behavioral inhibition in infancy was associated with AHR in adolescent and young adult rhesus monkeys, but was not associated with atopy [18]. Airway responsiveness, commonly assessed by recording the dosage of a bronchoconstrictor needed to increase airways resistance by a fixed amount, presents a much better measure of asthma than self- or parent-reports and is commonly used to confirm a diagnosis of asthma [19].…”
Section: Introductionmentioning
confidence: 57%
See 4 more Smart Citations
“…Decades of research have likewise demonstrated close similarity between humans and rhesus monkeys in behavioral and physiological measures of behavioral inhibition [16], [17]. In fact, in a recent retrospective study in our laboratory, we found that behavioral inhibition in infancy was associated with AHR in adolescent and young adult rhesus monkeys, but was not associated with atopy [18]. Airway responsiveness, commonly assessed by recording the dosage of a bronchoconstrictor needed to increase airways resistance by a fixed amount, presents a much better measure of asthma than self- or parent-reports and is commonly used to confirm a diagnosis of asthma [19].…”
Section: Introductionmentioning
confidence: 57%
“…At the end of this period, animals were returned to their mothers and their field corrals. We defined BI using criteria identical to that in our retrospective analysis of BI and airways response [18]: behaviorally inhibited animals were identified by low emotionality (based on focal animal observations), high vigilance (based on temperament ratings conducted at the end of the 25-hr period), and blunted cortisol response (determined seven hours after separation/relocation). Other laboratories have shown continuity of BI in both rhesus monkeys [26], [27] and humans [28][30] using similar measures.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations